2020
DOI: 10.21037/gs-20-791
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant docetaxel with or without carboplatin plus dual HER2 blockade for HER2-positive breast cancer: a retrospective multi-center Chinese study

Abstract: Background: This study aimed to compare the real-world efficacy and safety of the TCbHP regimen (docetaxel, carboplatin, trastuzumab and pertuzumab) and the THP regimen (docetaxel, trastuzumab and pertuzumab) as neoadjuvant therapy for Chinese patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Methods: We compared efficacy and safety outcomes from 72 Chinese patients with HER2-positive breast cancer who underwent neoadjuvant dual HER2 blockade plus TCb or T chemotherapy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
(41 reference statements)
3
21
2
Order By: Relevance
“…The use of carboplatin in our study might have also contributed to the difference. Carboplatin has been reported as part of the chemotherapy backbone for HER2-positive breast cancer [25,26]. The pCR rate in our study was also similar to that of pertuzumab plus TCH reported in the KRISTINE study (56%) [4].…”
Section: Discussionsupporting
confidence: 89%
“…The use of carboplatin in our study might have also contributed to the difference. Carboplatin has been reported as part of the chemotherapy backbone for HER2-positive breast cancer [25,26]. The pCR rate in our study was also similar to that of pertuzumab plus TCH reported in the KRISTINE study (56%) [4].…”
Section: Discussionsupporting
confidence: 89%
“…The most common adverse events found in our study were anaemia, weakness, neuropathy, and neutropenia. Diarrhoea was observed in our patients less frequently (26%) than in other studies, whereas most publications report the occurrence of diarrhoea in 40-56% of patients started on the treatment [8,9,27,32,33]. It should be noted, then, that we observed diarrhoea significantly more often in patients aged 60 years and older (71%) than in younger patients.…”
Section: Discussioncontrasting
confidence: 71%
“…In observational studies describing the everyday clinical practice, patients with no significant co-existing medical conditions and being younger are often selected for treatment with dualblockade anti-HER2 regimens, in particular TCbH-P [32,33]. The results of our study support the validity of such choices since, in particular for the group of ER-positive patients, the benefit of using a relatively toxic TCbH-P regimen is unlikely to carry any extra benefits and may lead to serious complications.…”
Section: Discussionsupporting
confidence: 55%
“…Human epidermal growth factor receptor 2 (HER2)-positive breast cancer is an aggressive subtype, with higher risks of recurrence and metastasis, and worse prognosis (3,4). The use of anti-HER2 monoclonal antibody as (neo)adjuvant therapy has improved survival in patients with HER2-positive early or locally advanced breast cancer (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%